Metal characterization of airborne particulate matters in a coastal region - Sahoo S.K.; Kumar A.V.; Yadav A.K.; Tripathi R.M. (My University, 2025)
The concentrations of suspended particulate matter in the air of the Orissa Sand Complex had an average value of 128 ± 10 µg m−3 in residential areas and 170 ± 8 µg m−3 in mining areas. PM10 levels in residential areas were found to have an average of 35 ± 10 µg m−3, in mining areas 45 ± 10 µg m−3. The distribution of some elements is also discussed here. Inhalation doses were observed to be higher in summer than in winter and the rainy season. The highest dose rate was for the age group of 1 year, and health risks were found to be highest for the same. For adults, inhalation dose and health risk are 1.3 times higher in mining than in residential areas. © 2016 Taylor & Francis.